Architecture of administrative buildings in an urban environment - Nogaibekova, М.Т. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article discusses the ways of formation and location of administrative buildings in the modern urban environment. The importance of the volume of the city administration in the structure of a modern large city, the creation of an attractive environment and the preservation of cultural values by synthesizing the latest techniques of architecture and urban planning and time-developed social attachments in urban space is noted.